Efficacy of the Responsive Classroom Approach: Results From a 3-Year, Longitudinal Randomized Controlled Trial. (June 2014) - Rimm-Kaufman, Sara E.; Larsen, Ross A. A.; Baroody, Alison E.; Curby, Timothy W.; Ko, Michelle; Thomas, Julia B.; Merritt, Eileen G.; Abry, Tashia; DeCoster, Jamie
This randomized controlled field trial examined the efficacy of the Responsive Classroom ( RC ) approach on student achievement. Schools ( n = 24) were randomized into intervention and control conditions; 2, 904 children were studied from end of second to fifth grade. Students at schools assigned to the RC condition did not outperform students at schools assigned to the control condition in math or reading achievement. Use of RC practices mediated the relation between treatment assignment and improved math and reading achievement. Effect sizes (ES) were calculated as standardized coefficients. ES relations between use of RC practices and achievement were .26 for math and .30 for reading. The RC practices and math achievement relation was greater for students with low initial math achievement (ES = .89). Results emphasize fidelity of implementation.